Upaya Hukum Penyelesaian Sengketa Penguasaan Tanah Adat (Studi Putusan Nomor 55/Pdt.G/2013/PN.Blg; 50/PDT/2015/ PT.MDN; 2753 K/PDT/2015) - Harefa, Steven Putra; Saidin, O.K.; Yefrizawati, Yefrizawati; Azwar, Tengku Keizerina Devi (Journal of Law & Policy Review, 2023)
The Toba Batak ethnic group living in the Samosir area is essentially a collection of traditional communities and generally are farmers who work on agricultural land and conceptualize land as not only an economic resource but also as a clan identity. The important role of land in human life, is that land is an object that is prone to disputes or disputes between humans. This type of research is empirical juridical research where the approach to the problem is carried out by examining the provisions of customary law in the Toba Samosir Regency. This research is normative and descriptive analysis, where this research attempts to describe, explain, and analyze the problems that arise, and then look for the correct answers as solutions to these problems. The results of the discussion of the problems that arise in this research are that legal efforts to resolve disputes over customary land tenure in Toba Samosir Regency can be carried out through non-litigation channels with consensus deliberation through traditional leaders and if a resolution cannot be obtained, then it will be taken through litigation. Legal efforts to resolve customary land tenure disputes in Toba Samosir Regency through litigation have provided legal certainty and legal protection.